Menilik Aspek-Aspek Sosial dalam Pendidikan Dasar dan Menengah - Mutholib, Abdul (Tarbawiyah Jurnal Ilmiah Pendidikan, 2016)
This article discuss about education that has the role of strategic and vital to the survival of a nation. Changes that occur on repeatedly can cause victims to the world of education, so education will lose its footing and flying following the direction of the wind of change that is going on. Then the social changes that occur either it concerns social values, behavioural patterns, organizations, civic institutions, layers in society, as well as with regard to power and authority (politics), must be faced with changes in the world of education. One trick is to maximise the social dimensions of education contained in the social aspects of education. As for the aspects include; (a) social aspects that are cultivated by education in schools, such as the cultural inheritance of the older generation to the younger generation; (b) the social aspects that affect education is characteristic of the dominant culture in certain regions where schools that exist; (c) the social aspects that play a role in education — and the bureaucratic organizational factors; (d) the social aspects that affect the educational system itself.